Integrating Performance Indicator Into the Audit Process Safety Management System - Hassan, C. R. Che; Pitt, M J; Wilday, A J (ASEAN Journal of Chemical Engineering, 2005)
The development of the audit method has included the identification of possible performance indicators at each level of the sociotechnical pyramid for a range of areas of work in which accidents have been shown to occur most frequently. The measurementof performance indicators is part of a feedback loop which causes safety improvements. Integration of performance indicators into the audit system has been tested at three operating chemical industries in Terengganu and Selangor in Malaysia. A summary of the weaknesses of the similar elements identified in the three audited plants is presented. Analysis on the approach used enables the identification of deficiencies in safety management aspects. Keywords: Accidents, audit, deficiencies, performance indicators, safety management, and sociotechnical pyramid.